Gold nanoparticles-modified titanium dioxide photoelectrode by screenprinting techniques - Shen, Junyang (2016)
Over the recent years, the discussion over environmental issues has been heated, especially due to the abnormal weather conditions and disasters which were being linked to greenhouse gases and global warming as the main causes. However the root of the problem is human use of non-renewable resources and the use of clean energy such as hydrogen has to be encouraged in order to solve the problem. There have been active research ongoing ever since a paper on photo electrolysis had been released in 1972 by Fukushima and Honda and the efficiency of the current water splitting process can still be further improved on so that its adoption will be more cost effective. For this experiment, Titanium Dioxide (TiO2) photoelectrode and spherical gold nanoparticles will be focused on and screen printing methodology will be used for the fabrication stage of modified TiO2 photo-electrodes. In the experiment, the two independent variables will be the particle sizes of the nanoparticles to be used and the amount of nanoparticles to be used. The dependent variables to be observed will be photocurrent density, reflectance and photocurrent conversion efficiency (PCE). The common controlled variables for the two independent variables include the apparatus to be used for the experiment, the intensity of the light source, the amount of TiO2 to be added, mixture stirring rate, curing temperature and curing time. An additional controlled variable for the first independent variable is the amount of nanoparticles used while that for the second independent variable is the particle size of the nanoparticles. The experimental results have been promising as it showed improvement to the efficiency of the TiO2 photo-electrode when sufficient amount of gold nanoparticles has been added and the larger the diameter of the nanoparticles is, the better the performance of the photo-electrode will be. On the contrary, if the amount of the 50 nanometres (nm) gold nanoparticles is at 1520 microliters (uL), the performance of the photo-electrode will decrease instead. This discovery will lead to further works to be done in the future where research towards the addition of noble nanoparticles such as silver or gold nanoparticles to metal oxides photo-electrodes can be focused on and perhaps lead to other significant improvements to the efficiency level of the water splitting process, promoting the use of clean energy to companies will therefore be easier.